ANALISIS YURIDIS PEMBATALAN PERKAWINAN INCEST (SEDARAH) DALAM KERANGKA UNDANG-UNDANG PERKAWINAN NOMOR 1 TAHUN 1974: (STUDI KASUS PUTUSAN PENGADILAN AGAMA PASIR PENGARAIAN NOMOR 255/PDT.G/2022/PA.PPG - Muhammad Fajrie; Almadison; Nofrizal; Hendri; Siska Amelya (Fakultas Hukum Universitas Pasir Pengaraian, 2023)
Marriage is a physical and spiritual bond between a man and a woman who become husband and wife with the aim of forming a happy and eternal family, based on the principles of the Almighty God. Marriage is considered sacred and important because it involves two families uniting to form a new family. A marriage can be declared invalid if it does not fulfill the requirements and pillars regulated by law or religion, or if there are obstacles that prevent it. The invalidity of a marriage can occur due to a lack of fulfillment of the pillars (annulled marriage) or conditions (an invalid marriage). Marriage conditions also include prohibitions originating from both religion and law, such as the prohibition on incestuous marriages. Cases of incestuous marriages have legal consequences, where the marriage can be declared null and void. However, this law does not apply retroactively to children born from incestuous marriages. This research is library research that uses a normative juridical approach; with secondary data sources in the form of copies of the Pasir Pengaraian Religious Court decision No.255/Pdt.G/2022/PA.Ppg and relevant laws and regulations. The data analysis method used is a normative qualitative approach to identify the legal consequences of incestuous marriage in case No.255/Pdt.G/2022/PA.Ppg. The results of the analysis show the legal consequences of incestuous marriages in the Pasir Pengaraian Religious Court Decision Number. No.255/Pdt.G/2022/PA.Ppg is an annulment of the marriage, but does not have an impact on the status of the children born from the